10th international conference on gas-liquid and gas-liquid-solid reactor engineering preface - Teixeira, J. A. (2011)
Following the success of the nine previous conferences on Gas–Liquid and Gas–Liquid–Solid reactor Engineering which were held at Columbus, OH, USA (1992), Cambridge, UK (1995), Kanagawa, Japan (1997), Delft, The Netherlands (1999), Melbourne, Australia (2001), Vancouver, Canada (2003), Strasbourg, France (2005), New Delhi, India (2007) and Montreal, Canada (2009) the tenth conference with the same theme is being held in Braga, Portugal, from 26 to 29 June 2011. This conference will cover all aspects of multiphase reactors related to progress made in the understanding, performance and operation of these reactors and will bring together scientists and engineers from universities and industry. The involvement of top researchers in Gas–Liquid and Gas–Liquid–Solid Reactor Engineering, the high quality of the papers presented and the line of continuity that has been guaranteed by the leadership of Prof. L.S. Fan of Ohio State University and the other members of the International Scientific Committee has made GLS a leading conference in Chemical Engineering. GLS has been held at regular intervals, every two years and in order to attract professionals across the globe, the venue of the GLS conference is shifted in a thoughtful manner amongst the continents. This conference has become an important meeting point for the exchange of views among scientists and engineers in one of the most important and complex issues in chemical engineering science and practice. The organizing committee is very pleased to be associated with Elsevier to have, as in most of the previous GLS editions, the proceedings of GLS10 published in Chemical Engineering Science (CES). As a result of a strict peer review process aiming at keeping with the highest standards of the journal, the GLS10 CES special issue includes a total of 39 papers, selected from the 150 Abstracts that were submitted to GLS10. Our sincere acknowledgments are due to Professor Anton P.J. Middelberg, the Executive Editor of CES, for his cooperation throughout the reviewing process. Also, we would like to express our gratitude to all the reviewers that made possible a timely publication of this special issue. Thanks are due to Genevieve Green from Elsevier for the excellent management of this special issue publication. Finally, it is our pleasure to dedicate this GLS10 CES special issue to Professor John Davidson as a tribute to his pioneering work and extraordinary contributions to Gas–Liquid and Gas–Liquid–Solid Reactor Engineering and to Chemical Engineering.